DUALISME MANUSIA DALAM LONTAR TUTUR BHAGAWAN ANGGASTYA PRANA - Wardana, I Ketut; Wariati, Ni Luh Gede; Astiti, Ni Wayan Sri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Lontar Bhagawan Anggastya Prana is a sacred manuscript with a Shaivist perspective, wherein Lord Shiva holds the highest position as the source of human creation (Bhuwana Alit), referred to as Sang Hyang Siwatman. This Lontar possesses unique characteristics compared to other Lontar manuscripts in Bali. It describes the process of human creation and the placement of sacred syllables on the human body, along with the Ista Dewata that governs them, as a teaching aimed at achieving liberation (Moksha). Therefore, it is essential to explore the dualistic concept of humanity according to Tutur Bhagawan Anggastya Prana. This study employs qualitative research, with the primary source being the Lontar Bhagawan Anggastya Prana from the collection of the Bali Cultural Documentation Center. The dualism of humanity in Tutur Bhagawan Anggastya Prana delves into the core of spiritual teachings concerning the dual nature or duality within humans. In this context, human dualism is depicted as two main aspects that form human existence: the physical aspect (stula sarira) and the spiritual or soul aspect (suksma sarira). Based on the analysis of the Lontar Tutur Bhagawan Anggastya Prana, it is revealed that the atman is a manifestation of Sang Hyang Śiwatma. Humans are imbued with Dewa, Kala, and Atma. The elements of the body are blessings from the gods, ultimately uniting into a holistic entity, the body. The sacred syllables in the human body are manifestations of Sang Hyang Widhi.